TRANSRADIAL APPROACH DURING PERCUTANEOUS CORONARY INTERVENTIONS. PART 1. EVIDENCE BASE FOR APPLYING A TRANSRADIAL APPROACH - Sh. T. Zhamgyrchiev; A. N. Samko; E. V. Merkulov; V. M. Mironov; I. V. Levitskiy; A. S. Tereshchenko; R. O. Shirokov; A. M. Gerasimov (Вестник рентгенологии и радиологии)
The use of the radial artery as an approach to percutaneous coronary interventions is becoming increasing popular now. The success of this approach depends on both the accumulated experience of an operator and a health care facility. The paper analyzes an investigation of the comparative characteristics of both a transradial approach and a transfemoral one and the impact of the former on the success of the procedure. It considers the role of the transradial approach in the present-day practice of X-ray endovascular diagnosis and treatment specialists and discusses the problems of education and choice of optimal clinical indications.